Preoperative assessment of coronary stenosis through ordinary chest CT for patients scheduled total hip or knee arthroplasty - Li, Yi; Wang, Yang; Ma, Ting; Duan, Xin; Si, Haibo (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCoronary artery calcium (CAC) is one of the main factors causing coronary stenosis and is often identified on ordinary chest computed tomography (CT). This study aims to explore the effectiveness of utilizing routine chest CT for preoperative coronary stenosis assessment in patients scheduled total hip or knee arthroplasty.Materials and methodsBetween July 2020 and July 2024, a retrospective analysis was conducted, and a total of 293 patients who intended to perform total hip or knee arthroplasty were included from 12,150 chest CT scans. Coronary artery calcium Score (CACS) was used to evaluate coronary stenosis based on the preoperative ordinary chest CT. Correlation between CACS and the degree of coronary artery stenosis determined via the coronary angiography (CAG) and the predictive ability of CACS for coronary artery stenosis ≥50% were analyzed.ResultsThe number of patients with CACS scores ranging from 0 to 499 was the largest, with 139 patients (47.44%). There were 88 patients (30.03%) with coronary artery stenosis ≥50%, 40 patients (13.65%) with ≥70%, and left anterior descending artery stenosis was the most common, with a total of 72 patients (24.57%). A strong correlation (R = 0.891, p < 0.001) between the degree of coronary stenosis and CACS was observed. A CACS threshold of ≥1,500 demonstrated a specificity of 100% and a positive predictive value (PPV) of 100% for coronary stenosis of ≥50%.ConclusionOrdinary chest CT is highly effective in evaluating the risk of coronary artery stenosis before total hip or knee arthroplasty, introducing a novel approach to facilitate our surgical decision-making.